2015
DOI: 10.1103/physrevc.91.014001
|View full text |Cite
|
Sign up to set email alerts
|

Role of pion exchange inηmeson photoproduction on the deuteron

Abstract: Incoherent η photoproduction on the deuteron is studied with the main emphasis on the role of final state interactions. In addition to the previously studied mechanisms of N N and ηN rescatterings, the role of an intermediate pion exchange is considered in detail, where first a pion is photoproduced on one nucleon and then rescatters into an η meson on the other, the spectator nucleon. It is found, that the role of this pion mediated contribution is comparable in size to that of ηN rescattering. Results for to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Theoretical results of Ref. [16] show visible sensitivity of some polarization observables to ηN and intermediate-pion (πN → ηN) FSI effects, but this issue is beyond the scope of the present paper.…”
Section: Comment On the η-Photoproduction Casementioning
confidence: 80%
See 2 more Smart Citations
“…Theoretical results of Ref. [16] show visible sensitivity of some polarization observables to ηN and intermediate-pion (πN → ηN) FSI effects, but this issue is beyond the scope of the present paper.…”
Section: Comment On the η-Photoproduction Casementioning
confidence: 80%
“…[16] and references therein), and the FSI effects were found to be important only in the very nearthreshold region. At higher energies, they are quite small [16], except for special kinematic configurations, where the IA contributions are suppressed. Theoretical results of Ref.…”
Section: Comment On the η-Photoproduction Casementioning
confidence: 96%
See 1 more Smart Citation
“…A slight enhancement in the backward direction due to the ηN → ηN rescattering is important for this agreement. Fix et al [20] also have done a comparable calculation, and found a rather minor role of the ηN → ηN rescattering mechanism in the η angular distribution at these energies. The slight underestimation of their results at backward angles ( Fig.…”
mentioning
confidence: 85%
“…1; the π-exchange mechanism was considered only in Ref. [20]. However, comparing the elementary amplitudes implemented in the previous models, the DCC model possesses unique and sound features such as: (i) the model describes all the meson-baryon and photoproduction amplitudes relevant to γd → ηpn in a unified manner; (ii) the model generates, by construction, off-shell amplitudes that are wellsuited for working with the Faddeev framework.…”
mentioning
confidence: 99%